Direct Electrochemical Reduction of Bicarbonate to Formate Using Tin Catalyst - Andreu Bonet Navarro (Electrochem, 2021)
Nowadays, the self-accelerating increase in global temperatures strengthens the idea that the cutting of CO2 emissions will not be enough to avoid climate change, thus CO2 from the atmosphere must be removed. This gas can be easily trapped by converting it to bicarbonate using hydroxide solutions. However, bicarbonate must be converted into a more valuable product to make this technology profitable. Several studies show great efficiency when reducing bicarbonate solutions saturated with pure CO2 gas to formate. However, those approaches don’t have a real application and our objective was to obtain similar results without pure CO2 saturation. The method consists of electroreduction of the bicarbonate solution using bulk tin (Sn) as catalysts. Tin is a relatively cheap material that, according to previous studies performed in saturated bicarbonate solutions, shows a great selectivity towards formate. The 1H NMR analysis of bicarbonate solutions after electroreduction show that, without pure CO2 gas, the faradic efficiency is around 18% but almost 50% for saturated ones. The formate obtained could be used to power formate/formic acid fuel cells obtaining a battery-like system, with greater energy density than common lithium batteries, but electroreduction efficiency needs to be improved to make them competitive.